Metal‐ and Base‐Free Direct N‐Arylation of Pyridazinones by Using Diaryliodonium Salts: An Anion Effect. Issue 8 (1st July 2018) - Xu, Bowen; Han, Jianwei; Wang, Limin
Abstract: An efficient N‐arylation of pyridazinones with diaryliodonium salts has been developed without using base or metal catalysts. The reaction tolerated a variety of both diaryliodonium salts and pyridazinone derivatives with diverse functional groups. Furthermore, a drug candidate for treatment of neuropathic pain was synthesized with this procedure in good yield. Abstract : Can you please pass the salt? An efficient N‐arylation of pyridazinones with diaryliodonium salts has been developed. The reaction did not require base or metal catalysts and tolerated a variety of diaryliodonium salts and pyridazinone derivatives with diverse functional groups.